Strategi Politik Identitas dalam Kemenangan Elektoral K.H. Rifa’i, S.H. pada Pemilu DPRD Provinsi Jambi 2024 - Nadilla Dewi Ningrum; Dori Efendi; Mariatul Qibtiyah (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study analyzes how strategi politik identitas is systematically used by K.H. Rifa’i, S.H. in winning the 2024 Provincial DPRD Election of Jambi in the Bungo–Tebo Electoral District. The main issue of this research stems from the strong influence of identitas keagamaan in the political behavior of Jambi’s majority Muslim society, making religious figures occupy a strategic position in electoral contests. This study aims to explain the process of mobilizing identitas keagamaan, utilizing social networks based on pesantren, and constructing a religious image as political capital that contributes to electoral victory. The analysis integrates the concepts of politik identitas and voter behavior as a foundation to understand how collective identity and psychological perceptions of society work in determining political preferences. This study employs a qualitative approach with a case study method, using interviews, observation, and document analysis as the main data collection techniques. The results show that identitas keagamaan, jaringan pesantren, relationships with local religious groups, and the use of religious symbols become determining factors that shape emotional closeness and political trust among the community. This strategy enabled K.H. Rifa’i to obtain the highest votes and outperform the incumbent candidate. The contribution of this research lies in a comprehensive mapping of how politik identitas operates within a local religious political context, and how this strategy can alter electoral configurations and political support patterns at the regional level.